Enhanced catalytic activity of hierarchically macro-/mesoporous Pt/TiO2 toward room-temperature decomposition of formaldehyde. Issue 4 (24th April 2015) - Qi, Lifang; Ho, Wingkei; Wang, Jinlong; Zhang, Pengyi; Yu, Jiaguo
<x xml:space="preserve">Abstract</x> Hierarchically macro-/mesoporous Pt/TiO2 exhibits excellent catalytic activity and recyclability toward catalytic decomposition of formaldehyde in air at room temperature.